Pengaruh Orientasi Pasar, Kreativitas dan Inovasi Produk terhadap Kinerja Pemasaran UMKM Kerupuk Tuiri di Kota Bengkulu - Safira, Nadila; Sofyan, Sofyan; Puspita, Veny (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine and analyze the effect of Market Orientation, Creativity and Product Innovation on Marketing Performance at UMKM Kerupuk Tuiri. In this study using non-probability sampling techniques, a sample of 180 respondents was taken. Data was collected using a questionnaire measured on a Likert scale. This study uses multiple linear regression analysis with the help of the SPSS version 22 program, the results of this study indicate that market orientation has no effect on marketing performance but creativity and product innovation have a partial effect on marketing performance. The results also show that market orientation, creativity and product innovation simultaneously affect marketing performance.